Synchronicity of Stress Wave Propagation in Bolt Body and Anchorage Medium - Sun, Bing; Xie, Jie-hui; Zeng, Sheng (ITB Journal Publisher, LPPM ITB, 2017)
Accurate assessment of anchoring quality depends on the accuracy of assessing stress wave velocity in the anchor system. Stress wave velocity is closely related to collaborative vibration and depends on the degree of bonding between anchor body and anchorage medium. Bonding differences can be large at different ages. Based on stress wave reflection methods, non-destructive testing of anchors was performed using sensors arranged at the same cross-section of the anchor body and anchorage medium, which showed stress wave synchronization. In the early stage of filling, stress wave synchronicity was poorer between the anchor body and mortar. Therefore, the anchor should not be treated as a composite material when determining its wave velocity. Once the mortar hardens, the stress waves become more synchronous and the anchor can be regarded as a composite material. Stress wave synchronicity between the anchor body and mortar is related to mortar age and anchorage length. The anchor length required to provide stress wave synchronization between the anchor body and mortar decreases with increasing mortar age. Stress wave velocity rules were derived for different ages to provide the basis for accurately determining the stress wave velocity in the anchor.